Terrorism and low intensity conflict in South Asian region - Mishra, Omprakash; Ghosh, Sucheta, 1949- (New Delhi : Manak Publications, 2003)
Contributed seminar articles
Includes bibliographical references and index
Keywords: Terrorism -- South Asia -- Congresses; Low-intensity conflicts (Military science) -- South Asia -- Congresses